Green fluorescent protein : properties, applications, and protocols - Chalfie, Martin; Kain, Steven (Wiley-Liss, 1998)
Green Fluorescent Protein: Properties, Applications, and Protocols is the first book devoted to this rapidly evolving reporter system. This collection of essays from pioneers in the field tackles both theory and practice, offering numerous case studies, examples, illustrations, and troubleshooting tips. The book clearly demonstrates how to tailor GFP to specific systems, maximize expression and enhance detection in a variety of organisms and cell types, generate variants with altered properties, explore new ways to use GFP, and more. Topics covered include: The discovery of GFP Bioluminescence and biofluorescence in nature Biochemical and physical properties of GFP The three-dimensional structure of GFP and its implications for function and design Molecular biology and modification of GFP Uses of GFP in various organisms, including prokaryotes, yeast, C. elegans, drosophila, plants, transgenic vertebrates, and mammalian cells Detailed protocols for the expression of GFP, specimen preparation, visualization and recording of GFP fluorescence, and GFP websites